Navigating the Future in the Brittle Era: A Systematic Literature Review of Academic Resilience and Learning Agility in Shaping University Students’ Future Orientation - Miranti Rasyid; Nanik Handayani; Aulia Suhesty (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The rapid and unstable transformations characteristic of the Brittle Era place university students in conditions of academic and career uncertainty, requiring strong adaptive capacities to maintain meaningful and sustainable future orientation. This study aims to systematically synthesize empirical evidence on the roles of academic resilience and learning agility in shaping students’ future orientation. A Systematic Literature Review (SLR) was conducted following the PRISMA protocol, analyzing 55 Scopus-indexed journal articles published between 2010 and 2026 through thematic and bibliometric approaches. The bibliometric findings indicate a growing scholarly interest in this field, reflected in an annual publication growth rate of 18.72% and an average of 21.84 citations per document, demonstrating the increasing academic relevance of these constructs. Thematic synthesis reveals three dominant patterns: academic resilience functions as a psychological resource that enables students to cope with academic stress and setbacks; learning agility serves as a proactive capability that promotes adaptability, continuous learning, and effective problem-solving; and the integration of both constructs provides a comprehensive adaptive framework that balances emotional stability with developmental growth. These findings highlight the strategic importance of incorporating resilience-building and agility-enhancement initiatives into higher education policies and curricula to strengthen students’ psychological readiness, career adaptability, and long-term capacity to navigate uncertainty. The review further suggests that fostering both resilience and learning agility is essential for developing future-oriented graduates capable of thriving in increasingly complex and unpredictable environments.Transformasi yang cepat dan tidak stabil yang menjadi ciri Era Brittle menempatkan mahasiswa pada kondisi ketidakpastian akademik dan karier, sehingga menuntut kapasitas adaptif yang kuat untuk mempertahankan orientasi masa depan yang bermakna dan berkelanjutan. Penelitian ini bertujuan untuk mensintesis secara sistematis bukti empiris mengenai peran resiliensi akademik dan learning agility dalam membentuk orientasi masa depan mahasiswa. Systematic Literature Review (SLR) dilakukan dengan mengikuti protokol PRISMA, dengan menganalisis 55 artikel jurnal terindeks Scopus yang dipublikasikan antara tahun 2010 hingga 2026 melalui pendekatan tematik dan bibliometrik. Temuan bibliometrik menunjukkan adanya peningkatan perhatian akademik terhadap topik ini, yang tercermin dari tingkat pertumbuhan publikasi tahunan sebesar 18,72% dan rata-rata 21,84 sitasi per dokumen, yang menunjukkan semakin tingginya relevansi akademik dari konstruk-konstruk tersebut. Sintesis tematik mengungkap tiga pola utama, yaitu: resiliensi akademik berfungsi sebagai sumber daya psikologis yang memungkinkan mahasiswa mengatasi stres dan hambatan akademik; learning agility berperan sebagai kapasitas proaktif yang mendorong kemampuan beradaptasi, pembelajaran berkelanjutan, dan pemecahan masalah yang efektif; serta integrasi kedua konstruk tersebut membentuk kerangka adaptif yang komprehensif dengan menyeimbangkan stabilitas emosional dan pertumbuhan perkembangan diri. Temuan ini menegaskan pentingnya mengintegrasikan program penguatan resiliensi dan peningkatan learning agility ke dalam kebijakan serta kurikulum pendidikan tinggi guna memperkuat kesiapan psikologis mahasiswa, kemampuan adaptasi karier, dan kapasitas jangka panjang dalam menghadapi ketidakpastian. Kajian ini juga menunjukkan bahwa pengembangan resiliensi dan learning agility secara bersamaan merupakan faktor penting dalam membentuk lulusan yang berorientasi masa depan dan mampu berkembang di tengah lingkungan yang semakin kompleks dan tidak terprediksi.